Albona : 20 gennaio 1599 - 20 gennaio 1899. - Martinuzzi, Giuseppina; Luciani, Luciano; Sillich, Villebaldo; Carbonetti, Pietro (Municipio, 1899)
O proslavi 300-godišnjice obrane Labina od uskočkih napada.